CORRECTIVE-PEDAGOGICAL APPROACHES TO DEVELOPING AUDITORY-SPEECH SKILLS IN VISUALLY IMPAIRED CHILDREN (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article provides a scientific analysis of corrective-pedagogical approaches aimed at developing auditory-speech skills in visually impaired children. Methods for forming auditory-speech functions are examined based on the theory of compensatory mechanisms, principles of special pedagogy, and modern audiological technologies. The results of experimental work conducted in special educational institutions of the Fergana region are presented. The findings confirm the necessity of organizing the development of auditory perception in visually impaired children on the basis of a differentiated approach.